2017
DOI: 10.1111/avj.12659
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of an Australian strain of canid alphaherpesvirus 1

Abstract: Objective Characterisation of a complete genome sequence of an Australian strain of canid alphaherpesvirus 1 (CHV-1) and its phylogenetic relationship with other varicellovirus species.Methods Standard pathology and PCR methods were used to initially detect herpesvirus in hepatic tissue from an infected 4-week-old Labrador Retriever puppy. The complete CHV-1 genome was sequenced using next-generation sequencing technology followed by de novo and reference assembly, and genome annotation.Results The CHV-1 genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…The sample was stored in appropriate conditions by the Veterinary Diagnostic Laboratory (VDL), Charles Sturt University under the accession number CS16-4047. Animal sampling was obtained in accordance with approved guidelines set by the Australian Code of Practice for the Care and Use of Animals for Scientific Purposes (1997) and approved by the Charles Sturt University Animal Ethics Committee (Research Authority permit 09/046), and the total genomic DNA was extracted using an established protocol (Sarker, Das, et al 2017;Sarker, Das, et al 2018). The genomic library preparation and sequencing was performed according to the published protocol (Sarker, Roberts, et al 2017;Sarker, Isberg, et al 2018;Sutherland et al 2019).…”
mentioning
confidence: 99%
“…The sample was stored in appropriate conditions by the Veterinary Diagnostic Laboratory (VDL), Charles Sturt University under the accession number CS16-4047. Animal sampling was obtained in accordance with approved guidelines set by the Australian Code of Practice for the Care and Use of Animals for Scientific Purposes (1997) and approved by the Charles Sturt University Animal Ethics Committee (Research Authority permit 09/046), and the total genomic DNA was extracted using an established protocol (Sarker, Das, et al 2017;Sarker, Das, et al 2018). The genomic library preparation and sequencing was performed according to the published protocol (Sarker, Roberts, et al 2017;Sarker, Isberg, et al 2018;Sutherland et al 2019).…”
mentioning
confidence: 99%
“…The second genetic paper describes the sequencing of canine alphaherpes virus 1 (CHV1), the causative agent of a severe necrotising and haemorrhagic disease in neonatal puppies. 4 The virus was detected in hepatic tissue from a puppy from an affected litter, all of which died. Results showed that the nucleotide sequence had a surprising similarity to a virus isolated from the UK and will provide further information on the genetics and evolution of the herpes viruses.…”
Section: Small Animalsmentioning
confidence: 97%
“…The second genetic paper describes the sequencing of canine alphaherpes virus 1 (CHV1), the causative agent of a severe necrotising and haemorrhagic disease in neonatal puppies . The virus was detected in hepatic tissue from a puppy from an affected litter, all of which died.…”
Section: Small Animalsmentioning
confidence: 99%
“…Additionally, a further 6 exudative poxvirus lesions from another 3 Northern Australian crocodile farms were included. DNA extraction from the collected samples was performed according to our previously published protocols [16,17]. Briefly, exudative pox lesions from individual crocodiles were aseptically dissected and mechanically homogenized in lysis buffer using disposable tissue grinder pestles and transferred into a 1.5 mL microcentrifuge tube (Eppendorf, Hamburg, Germany).…”
Section: Virus Genome Sequencing and Analysesmentioning
confidence: 99%